Sustainability and performance in operations management research - Magon, Renata Bianchini; Thomé, Antônio Márcio Tavares; Ferrer, Ana Luiza Carvalho; Scavarda, Luiz Felipe (Journal of cleaner production, 2018)
Interest in sustainability and its relation to performance has grown significantly among practitioners and operations management (OM) scholars. However, there is still a paucity of research on the antecedents and drivers of sustainability, as well as on the relationship between sustainability and performance. Moreover, the literature offers contradictory results on this relationship. Therefore, the goal of this paper is to provide a research synthesis about the overall state of the art of empirical research on the impact of sustainability management practices on performance, encompassing social and environmental dimensions. To achieve this goal, the authors develop a rigorous systematic review of the extant literature on sustainability relationships with firm performance, emphasizing the under-researched area of causal models of sustainability and operational performance. This research is a first attempt to go beyond the highly dispersed work on the subject, aiming to provide more generalizable evidence about theories, methods and findings. The synthesis embraces 231 papers in total and identifies the main variables on causal models depicting the relationships between sustainability and performance, analyses how the studies on the subject are conducted, and investigates the impact and the mechanisms through which sustainability affects operational performance (OP). Overall, there are positive effects of sustainability on performance, such as lower costs, better delivery and product quality, enhanced volume and mix flexibility, although different mechanisms drive the sustainability-performance links and they differ according to contexts. The study outlines implications for practice and future research. •A research synthesis on the impact of sustainability on performance is provided.•Variables on causal models linking sustainability and performance are identified.•The paper evaluates how studies on sustainability and OP were conducted.•The impact and the mechanisms through which sustainability affects OP are analysed.